Induction of Pluripotent Stem Cells from Primordial Germ Cells by Single Reprogramming Factors123. (25th February 2013) - Nagamatsu, Go; Kosaka, Takeo; Saito, Shigeru; Honda, Hiroaki; Takubo, Keiyo; Kinoshita, Taisuke; Akiyama, Hideo; Sudo, Tetsuo; Horimoto, Katsuhisa; Oya, Mototsugu; Suda, Toshio
Abstract Germ cells are similar to pluripotent stem cells in terms of gene expression patterns and the capacity to convert to pluripotent stem cells in culture. The factors involved in germ cell development are also able to reprogram somatic cells. This suggests that germ cells are useful tools for investigating the mechanisms responsible for somatic cell reprograming. In this study, the expression of reprograming factors in primordial germ cells (PGCs) was analyzed. PGCs expressed Oct3/4, Sox2, and c‐Myc but not Klf4. However, Klf2, Klf5, Essrb, or Essrg, which were expressed in PGCs, could compensate for Klf4 during somatic cell reprograming. Furthermore, PGCs could be converted to a pluripotent state by infection with any of the known reprogramming factors (Oct3/4, Sox2, Klf4, and c‐Myc). These cells were designated as multipotent PGCs (mPGCs). Contrary to differences in the origins of somatic cells in somatic cell reprogramming, we hypothesized that the gene expression levels of the reprogramming factors would vary in mPGCs. Candidate genes involved in the regulation of tumorigenicity and/or reprogramming efficiency were identified by comparing the gene expression profiles of mPGCs generated by the exogenous expression of c‐Myc or L‐Myc. STEM CELLS2013;31:479–487